Colonoscopy as a useful tool in determining the transition zone in transanal endorectal pull-through in Hirschsprung's disease - Lourenção, Pedro Luiz Toledo de Arruda [UNESP] (2012)
Faculdade de Medicina de Botucatu Departamento de Cirurgia e Ortopedia, S/n CEP 18618-970, Botucatu, SP